AB0933 PHYSICAL ACTIVITY DECREASES PAIN AND INFLAMMATION IN GOUT PATIENTS. (2nd June 2020) - Schlesinger, N.; Jablonski, K.; Schwarz, E.; Young, N.
Abstract : Background: Despite the high prevalence of gout, there has been little investigation into the relationship between physical activity and gout. Objectives: To investigate whether physically active gout patients, as assessed by the International Physical Activity Questionnaire (IPAQ) long form, have lower pain scores, decreased inflammation, assessed by C-reactive protein (CRP) levels and less flares. Methods: During scheduled appointments, gout patients not experiencing a flare at the time of visit were recruited from our clinics and consented to participate in the study. IPAQ were completed. Clinical data collected during the visit included age, years since diagnosis, flares per year, perceived pain at the time of visit and in the past 4 weeks, and C-reactive protein (CRP) levels. Results: Thirty gout patients were recruited. Ages 31-86 (mean 61); duration of gout: one- 43 years (mean 9). IPAQ, separated gout patients into physically active (n=16) and physically inactive cohorts (n=14) (p<0.001. Physically active gout patients had over 12-fold fewer gout flares per year (p<0.01); 10-fold less CRP (p<0.01, a 4.6-fold decrease in perceived pain at the time of visit (p<0.01), and a 2.8-fold decrease in perceived pain over the past 4-week period (p<0.05). Conclusion: This is the first study using a validated physical activity tool, IPAQ, to assess physical activity in gout patients. In this study, physically active gout patients were found to have lower CRP levels, less flares per year, and decreased pain perception compared to those that are not physically active, highlighting, the importance of incorporating physical activity as a possible adjunct treatment option during intervals between flares. References: [1]Benatti FB, Pedersen BK. Exercise as an anti-inflammatory therapy for rheumatic diseases-myokine regulation. Nat Rev Rheumatol 2015;11:86-97. [2]Hagströmer M, Oja P, Sjöström M. The International Physical Activity Questionnaire (IPAQ): a study of concurrent and construct validity. Public Health Nutr 2006;9:755-62. [3]Young NA, Jablonski K, Sharma J, Thomas E, Snoad B, Hampton J, et al. Low and Moderate Intensity Exercise Suppresses Inflammatory Responses in an Acute Mouse Model of Gout and Suggests Therapeutic Efficacy [abstract]. Arthritis Rheumatol. 2017;69 (suppl 10). Disclosure of Interests: Naomi Schlesinger Grant/research support from: Pfizer, AMGEN, Consultant of: Novartis, Horizon Pharma, Selecta Biosciences, Olatec, IFM Therapeutics, Mallinckrodt Pharmaceuticals, Speakers bureau: Takeda, Horizon, Kyle jablonski: None declared, Emmy schwarz: None declared, Nicholas Young: None declared